Mycobacterium tuberculosis Methyltransferase Rv1515c Can Suppress Host Defense Mechanisms by Modulating Immune Functions Utilizing a Multipronged Mechanism - Rani, Anshu; Alam, Anwar; Ahmad, Faraz; P., Manjunath; Saurabh, Abhinav; Zarin, Sheeba; Mitra, Dipendra Kumar; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Molecular Biosciences, 2022)
Mycobacterium tuberculosis (M.tb) gene Rv1515c encodes a conserved hypothetical protein exclusively present within organisms of MTB complex and absent in non-pathogenic mycobacteria. In silico analysis revealed that Rv1515c contain S-adenosylmethionine binding site and methyltransferase domain. The DNA binding and DNA methyltransferase activity of Rv1515c was confirmed in vitro. Knock-in of Rv1515c in a model mycobacteria M. smegmatis (M.s_Rv1515c) resulted in remarkable physiological and morphological changes and conferred the recombinant strain with an ability to adapt to various stress conditions, including resistance to TB drugs. M.s_Rv1515c was phagocytosed at a greater rate and displayed extended intra-macrophage survival in vitro. Recombinant M.s_Rv1515c contributed to enhanced virulence by suppressing the host defense mechanisms including RNS and ROS production, and apoptotic clearance. M.s_Rv1515c, while suppressing the phagolysosomal maturation, modulated pro-inflammatory cytokine production and also inhibited antigen presentation by downregulating the expression of MHC-I/MHC-II and co-stimulatory signals CD80 and CD86. Mice infected with M.s_Rv1515c produced more Treg cells than vector control (M.s_Vc) and exhibited reduced effector T cell responses, along-with reduced expression of macrophage activation markers in the chronic phase of infection. M.s_Rv1515c was able to survive in the major organs of mice up to seven weeks post-infection. These results indicate a crucial role of Rv1515c in M.tb pathogenesis.